Comparison of Agitators Performance for Particle Suspension in Top-Covered Unbaffled Vessels - A. Tamburini (Chemical Engineering Transactions, 2015)
Power savings is a problem of crucial importance nowadays. In process industry, suspension of solid particles into liquids is usually obtained by employing stirred tanks, which often are very power demanding. Notwithstanding tanks provided with baffles are traditionally adopted for this task, recent studies have shown that power reductions can be obtained in top-covered unbaffled vessels. In the present work experiments were carried out in a top-covered unbaffled vessel with a diameter T=0.19m and filled with distilled water and silica particles. Two different turbines were tested: a standard six-bladed Rushton Turbine (RT) and a 45° four bladed Pitched Blade Turbine (PBT). For the case of the PBT both the up-pumping (PBT-Up) and the down- pumping (PBT-Down) operation mode were tested. Two different impeller sizes D (T/3 and T/2) and clearances C (T/3 and T/10) were investigated. The effects of particle size and concentration were also assessed. Investigations concern the assessment of the minimum impeller speed for complete suspension (Njs) along with the measurement of the relevant power consumption (Pjs) aiming at identifying the most efficient tank-turbine configuration among those investigated here. Results were also compared with corresponding ones pertaining to baffled tanks (obtained via correlations available in the literature). Results have shown that the RT with D=T/3 and C=T/3 and the PBT-Up with D=T/2 and C=T/10 appear to be the most convenient (least power demanding) options. Finally, a significant power saving with respect to the most efficient baffled configurations was observed thus confirming the convenience of operating solid-liquid suspensions in an unbaffled system for all those processes where the mixing time is not a limiting factor.